PENGARUH PEMBERIAN OKSITOSIN DAUN KATU DAN DAUN LAMPES TERHADAP SEKRESI AIR SUSU DAN GAMBARAN HISTOLOGI KELENJAR AMBING PADA MENCIT - I.B. Rai Pidada (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 1999)
A comparative study on the effect of oxytocin, extracted leaf of katu (Sauropus androgynous, Merr) and lampes (Ocimum sanctum, Linn) against secretions of milk and histologically mammary gland of mice was carried out under laboratory conditions. The study was designed by using totally 40 mice pp and divided into four groups treatment which consisted 10 females mice post partum (pp) of each group. The control group, katu (S.androginus), lampes (O. sanctum), and oxytosin were given orally 0.5 ml physiological solution, 10 mg/0.5 ml leaf extract of S. androgynus , 10 mg/0.5 ml leaf extract of O. sanctum and 0.1 IU oxytocin intramuscular, respectively. The treatment were started on day fourt to 21th of lactation period. The data were observed on day 6th, 9th, 12th, 15th, of lactation period and than on day 21th the mice were killed to prepare histologically of mammary glands. The data analyzed by ANOVA and LSD test. The result of the study showed that the secretion of the milk on the mice were not significantly different among of fourth groups. However between S. androgynous and O. sanctum group accured an increasing on secretion of milk productions. The diameter of alveolus pit of mammae lobus gland were not significantly different amongs the fourth group, but the number of alveolus of mammae lobus gland were significantly different among oxytocin, S. androgynous, and O. sanctum group and between the group of O. sanctum and control.